Suprasellar epidermoid cyst: a rare cause of painless progressive bilateral vision loss-case report with clinico-radiological correlation - Chauhan, Gaurav; Singh, Vivek; Phadke, R. V.; Yadav, Sapna (International Journal of Research in Medical Sciences, 2018)
Intracranial epidermoid cysts are relatively rare lesions. They result from inclusion of ectodermal elements during time of neural tube closure. This lesion could rarely be acquired due to post-surgical or post traumatic implantation of the ectodermal components. They typically present in middle age group patients with evidence of loco-regional mass effect on adjacent structures. We present a clinico-radiological case report of the 27-year-old female patient who presented with painless progressive bilateral vision loss for last 4 months.